Pengaruh Belanja Langsung dan Belanja Tidak Langsung terhadap Kemiskinan - Jouzar Farouq Ishak (Jurnal Akuntansi dan Bisnis, 2017)
ABSTRACT The research purposed to examine the finding of a significant influence on direct expenditure and indirect expenditure to poverty condition in the regency or city government in West Java Province, both partially and simultaneously. Population in this research was the citizen of regency or city government in West Java Province. The data obtained was a combination of time series data and cross-section data or commonly referred to as panel data. The technique applied in obtaining sampling was purposive sampling. The researcher equipped the regression analysis which is a form of analysis in regression which is hierarchal design to determine relation between two variables which in regression equation contains element of interaction between two or more independent variables. The results showed that direct expenditure had negative significant effect on poverty in district or city government in West Java Province. Yet, indirect expenditure had also positive significantly affected poverty in the similar area as well. It could be summarized that both direct and indirect expenditure had the positive significant effect on poverty in the regency or city government in West Java Province. Keywords: direct expenditure, indirect expenditure, poverty